Contribution of different sources and origins of nitrogen in above- and below-ground structures to the partial nitrogen balance in soybean. - Kehoe, Esteban (2022)
Aims: Most studies that quantified the biological N fixation (BNF) and partial N balances of soybean have ignored the belowground structures. Our objectives were to evaluate the contribution of belowground structures to the partial N balance of soybean and to identify the origin (soil or BNF) and source (apparent remobilization or current gain during the seed-filling period) of seed N. Methods: Biomass, BNF, and N uptake coming from different N sources and origins, including belowground structures, were quantified in a two-year field study involving two soybean genotypes (MG IV and V) and two water availability conditions (rainfed and irrigated). Results: The inclusion of BNF-derived N present in belowground components (which averaged +12 kg N ha−1 at R7) changed the results of the partial N balances from negative to positive. BNF was the main origin of seed N, accounting for 73 and 79% of seed N under water stressed and non-stressed conditions, respectively. Regarding the seed N source, apparent remobilization was the main contributor to seed N under water stress, whereas current N gain was the main contributor to seed N in unstressed plants. Conclusions: We conclude that i) the root system retains a relevant proportion of the atmospheric N fixed during the crop cycle and should be included in the partial N balance estimations; and ii) BNF is the main origin of seed N, even under contrasting growing conditions.